Analysis of maternal health service problems in the maternal and child health (KIA) program of the Konawe District Health Office - Wa Anasari; Suhartati Suhartati; Arbiyah Arbiyah; Eka i Syafitri Wahyuni; Sitti Hastati (Alma Ata University Press, 2021)
Background: One form of service in the MCH program is services for pregnant women which consist of health services for pregnant women, maternal health, postpartum health, handling of obstetric complications, and contraceptive services, all of which aim to ensure protection for pregnant women and / or fetuses. This is closely related to efforts to reduce maternal mortality (MMR). Objectives: The research objective was to determine the priority of health problems, find the root of health problems and provide alternative solutions to problems in health care for pregnant women Methods: The research method used is descriptive research using secondary data sources to determine the priority of the problem by means of a Focus Group Discussion (FGD) involving decision makers at the Konawe District Health Office. The formulation of alternative solutions is carried out after the root causes are identified using Ishikawa or Fishbone diagrams. The priority of the root cause of the problem is carried out using the Capability Accessibility Readiness Leverage (CARL) method. Results: The results show that the low K1 and K4 coverage of pregnant women health services is the main priority problem. The root cause of the problem that must be prioritized to be resolved is that socialization to teenagers / prospective brides (catin) about marriage at a young age is still a major problem that must be followed up. The alternative that is given as a solution is to provide counseling using innovative and attractive media to make it easier to understand.Conclusions: The priority of health problems in the MCH Program of the Konawe District Health Office is the problem of health services for pregnant women with K1 and K4 coverage. The root of the problem of socialization among adolescents / catin about marriage at a young age is still lacking is the level of education, knowledge, employment, counseling media are less innovative and interesting, the frequency of counseling and the size of the area are not proportional to the available resources. An alternative solution is socialization to teenagers/catin about marriage at a young age is still lacking by using innovative and interesting counseling media so that it is easy to receive and understand the information conveyed.